ON gr*-HOMEOMORPHISM IN TOPOLOGICAL SPACES - Indirani, K. (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
This paper deals with gr*-closed maps, gr*-open maps, gr*-homeomorphism, gr**-homeomorphism and study their properties. Using these new types of maps, several characterizations and properties have been obtained. Â  Keywords: gr*-closed maps, gr*-open maps, gr*- homeomorphism, and gr**- homeomorphism.